Islamization of Science in the Era of Society 5.0: Study of al-Attas' Thought - Muh Hanif; Hani Prasetianingtiyas (International Journal of Social Science and Religion (IJSSR), 2023)
This article intends to examine and examine the idea of the Islamization of contemporary science, especially in the era of society 0.5 in the view of Syed Muhammad Naquib al-Attas. The use of descriptive methods with a philosophical approach is used for this research. By interpreting various sources, since the birth of the idea, the Islamization of knowledge has become an attraction for Muslim scholars. Al-Attas dared to express an opinion contrary to the western term not to deify science (science). This idea is relevant to the current conditions where people's lives and science are supported by technology that the West mainly creates. The science currently developing is much out of Islamic values and brings disaster to humans. Hence, the importance of human awareness is to return to religion and not deify knowledge so that excessive fanaticism arises.